1971
DOI: 10.1128/aem.22.1.44-48.1971
|View full text |Cite
|
Sign up to set email alerts
|

Antigens of Pasteurella tularensis: Preparative Procedures

Abstract: Ether-water (EW) extraction of Pasteurella tularensis produced better antigens than five other chemical procedures. EW extracts produced from stationary-phase, liquid-grown, saline suspensions of strain SCHU S4 cells regularly induced agglutinin and precipitin formation in rabbits. Mice, guinea pigs, and monkeys also responded to EW extracts but with lower antibody levels. The use of strains of lower virulence, acetone-dried cells, organisms grown on a solid medium, and abbreviated extraction conditions all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
1
4
0
1
Order By: Relevance
“…DISCUSSION Antigen for immunoprecipitation was more efficiently extracted from F. tularensis cells by ether-water treatment than by phenol-water extraction. This is in accordance with immunoprecipitation studies on various extracts of F. tularensis (20). To take full advantage of the high sensitivity of ELISA, the specificity of the antigen prepared is important (18).…”
Section: -supporting
confidence: 72%
See 1 more Smart Citation
“…DISCUSSION Antigen for immunoprecipitation was more efficiently extracted from F. tularensis cells by ether-water treatment than by phenol-water extraction. This is in accordance with immunoprecipitation studies on various extracts of F. tularensis (20). To take full advantage of the high sensitivity of ELISA, the specificity of the antigen prepared is important (18).…”
Section: -supporting
confidence: 72%
“…Accordingly, ether-water extraction is known to be an efficient way to release antigens (21,22,25,26). When compared by immunoprecipitation, this extraction procedure is better than several others, including phenol-water extraction (20). Ether-water extracts, however, have not previously been utilized in ELISA or the lymphocyte stimulation test.…”
mentioning
confidence: 99%
“…Several biochemical tests have been described that allow differentiation of F. tularensis subspecies and biovars [117]. An agglutination assay in which specific sera are used has also been used for identification of F. tularensis , but does not allow identification of the biovar [155]. More accurate differentiation is best achieved with molecular biological techniques.…”
Section: Species and Subspecies Identificationmentioning
confidence: 99%
“…Some of these values are low, but the combination of some of the PCR methods allow us to achieve DI of 0.8 to 0.9. These results can be considered excellent, especially if both the small area from which the Spanish isolates were recovered and previous information about typing tools for Francisella strains are taken into account (the DI observed for serologic methods is 0, as only one antigenic group has been described so far [3,12], and DNA methods have been unable to discriminate between F. novicida and F. tularensis [5]). On the other hand, the results in this study were clearly different from those reported by Vila et al (16), who found that the RAPD assay was less discriminating than rep-PCR methods for typing of the Acinetobacter calcoaceticus-A.…”
Section: Discussionmentioning
confidence: 99%
“…The correct identification of strains of F. tularensis can be verified by agglutination with specific antisera. However, since strains of Francisella have similar antigenic compositions (to date all of the isolates belong to a unique antigenic group), it is not possible to distinguish the different subspecies or types from each other by this method (12). Subspecies of F. tularensis have been differentiated by biochemical tests (10) and by using probes specific to the 16S rRNAs of each of the two main subspecies (4,14).…”
mentioning
confidence: 99%